IMPACT OF MODERN TECHNOLOGY IN THE FIELD OF EDUCATION - Malabika Hazarika (International Journal of Advanced Science and Technology, 2020)
Technology has certainly changed the way that we live . Technology plays an important role in every sphere of life , today and of course education is no exception in that .It has affected and impacted the way things are presented and taught in the classroom to the students. It has greatly impacted on the material which are used and the way we use these materials to teach students in the school. Technology in the classroom became more predominent by improved learning, increased engagement of students and virtual programmes.